Can multiple contractors self-regulate their joint service delivery? A serious gaming experiment on road maintenance planning. Issue 2 (1st February 2021) - Scharpff, Joris; Schraven, Daan; Volker, Leentje; Spaan, Matthijs T. J.; de Weerdt, Mathijs M.
Abstract: The next step in the use of innovative, dynamic and performance-based contracts for service delivery by contractors could be use of monetary incentives to stimulate self-regulation of the network. Because it is currently unclear how performance-based payments in network tenders can effectively encourage network members to coordinate their own operations, a serious game was performed that simulates road maintenance planning to study changes in decision making and the emergence of network coordination. The experiments show that monetary incentives influence decision making, but their effect may be opposite to their intended aim and can lead to a competitive network. It was, however, also found that this competitiveness is not shown in networks where members are familiar with each other. This leads to the conclusion that penalty-based incentive mechanisms probably interfere with self-regulation and that the social dimension of contractor collaboration is paramount to the success of network-based contracting of construction activities.